Concept of operations of an ATC tool for trajectory optimization - Zammit-Mangion, David (International Council of the Aeronautical Sciences (ICAS), 2016)
This paper presents the Concept of Operations (Con-Ops) associated with integrating a quasi-real-time ground-based trajectory optimization tool in the Air Traffic Control system. The tool is intended to be used a few minutes before a climb or descent to generate trajectories with minimual fuel burn which take into account the latest operational considerations.
© The Authors